2012
DOI: 10.1073/pnas.1120063109
|View full text |Cite
|
Sign up to set email alerts
|

DNA charge transport as a first step in coordinating the detection of lesions by repair proteins

Abstract: Damaged bases in DNA are known to lead to errors in replication and transcription, compromising the integrity of the genome. We have proposed a model where repair proteins containing redoxactive [4Fe-4S] clusters utilize DNA charge transport (CT) as a first step in finding lesions. In this model, the population of sites to search is reduced by a localization of protein in the vicinity of lesions. Here, we examine this model using single-molecule atomic force microscopy (AFM). XPD, a 5′-3′ helicase involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(138 citation statements)
references
References 51 publications
7
129
0
2
Order By: Relevance
“…DNA charge transport has been suggested to activate MAPK signaling. 56,57 MAPK activation was also suggested from transcriptome analysis of another NER mutant, ercc-1 39 , where we found a strong correlation between genes regulated by the PMK-1 p38 MAPK and the ercc-1 data set. Together, these results suggest that NER function is not lifespan-limiting in C. elegans partially due to an adaptive transcriptome reprogramming involving activation of p38 MAPK stress-response signaling.…”
Section: Does Accumulation Of Cyclopurines Cause the Reduced Lifespansupporting
confidence: 74%
“…DNA charge transport has been suggested to activate MAPK signaling. 56,57 MAPK activation was also suggested from transcriptome analysis of another NER mutant, ercc-1 39 , where we found a strong correlation between genes regulated by the PMK-1 p38 MAPK and the ercc-1 data set. Together, these results suggest that NER function is not lifespan-limiting in C. elegans partially due to an adaptive transcriptome reprogramming involving activation of p38 MAPK stress-response signaling.…”
Section: Does Accumulation Of Cyclopurines Cause the Reduced Lifespansupporting
confidence: 74%
“…Remarkably, when its localization near DNA damage is studied by AFM, XPD is found to cooperate with EndoIII to promote redistribution around mismatches, despite the fact that these proteins are derived from entirely different organisms. 136 This result highlights the universal nature of DNA CT as a mechanism for long-distance biological signaling and coordination of protein activities even, between proteins of diverse structure and function.…”
Section: Dna Ct On Surfacesmentioning
confidence: 87%
“…[4][5][6] Many efforts [7][8][9][10][11][12][13][14][15][16] have been devoted to understanding the mechanism of charge transfer and transport in DNA. From an electrical device perspective, double barrier resonant tunneling structures, 17 spin specific electron conductor, 18,19 field effect transistor, 20 trinary logic, 21 optomechanical molecular motor, 22 negative differential resistance, 23 detection of lesions by repair proteins 24 and doping 25 are in principle possible with DNA. Furthermore, recent work has also shown that it is possible to detect diseases by measuring the electrical conductivity of DNA.…”
Section: Introductionmentioning
confidence: 99%